2012
DOI: 10.1242/jeb.061531
|View full text |Cite
|
Sign up to set email alerts
|

Differential limb loading in miniature pigs (Sus scrofa domesticus): a test of chondral modeling theory

Abstract: SUMMARYVariation in mechanical loading is known to influence chondrogenesis during joint formation. However, the interaction among chondrocyte behavior and variation in activity patterns is incompletely understood, hindering our knowledge of limb ontogeny and function. Here, the role of endurance exercise in the development of articular and physeal cartilage in the humeral head was examined in 14 miniature swine (Sus scrofa domesticus). One group was subjected to graded treadmill running over a period of 17 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 68 publications
(117 reference statements)
1
18
0
Order By: Relevance
“…This study examined transient knee joint loads during the drop-landing response and the effect of drop height and instruction cues on knee joint loads. Further, this study took steps toward a development of standardized exercise task to examine the effect of acute bouts of mechanical loading on bone and cartilage metabolism in humans, since previous research has been focused on animal models [15, 16]. Consistent with previous literature [24, 30], we found that the knee joint compression force increased with drop height and the instruction to land stiffly.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study examined transient knee joint loads during the drop-landing response and the effect of drop height and instruction cues on knee joint loads. Further, this study took steps toward a development of standardized exercise task to examine the effect of acute bouts of mechanical loading on bone and cartilage metabolism in humans, since previous research has been focused on animal models [15, 16]. Consistent with previous literature [24, 30], we found that the knee joint compression force increased with drop height and the instruction to land stiffly.…”
Section: Discussionsupporting
confidence: 83%
“…Short-term and acute responses of skeletal and articular cartilage metabolism to physical activity have been reported [1214]; however, findings across studies are difficult to compare because the types of activities and research methodology are not standardized [14]. Traditionally, animal models have been used to examine the effects of mechanical loading on bone and articular cartilage [15, 16]; however, a comparable and standardized model to assess the acute response of bone and cartilage turnover to various levels of mechanical loading has not yet been clearly defined in humans [17]. To improve clinical utility of exercise that may result in a net formation of bone and cartilage in humans, it is important to have a standardized approach that allows researchers to examine responses, to quantify doses of mechanical loads, and to determine if a dose-response exists [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Ravosa et al (Ravosa et al, 2008) found that symphyseal hard tissues in older rabbits maintain a level of plasticity unlike that of the TMJ, which exhibits decreased biomineralization and apparent increases in porosity. The notion that tissue plasticity might be site-specific is supported by comparisons of proximal limb joints in growing pigs subjected to exercise-induced dynamic loading, where differences in bone and cartilage responses were noted between the proximal femur and proximal humerus in the same experimental subjects (Congdon et al, 2012). Osteogenic responses of cortical bone to exercise may also vary along the length of a limb element, with distal regions exhibiting more pronounced morphological changes to altered mechanical stimuli (Hamrick et al, 2006; see also Hsieh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Different regions of the musculoskeleton do not always respond to mechanical load regimes in the same manner (Biewener and Gillis, '99;Pearson and Lieberman, 2004;Plochocki et al, 2008;Congdon et al, 2012). In this study, we investigated how different locomotor regimes-climbing and running exercise-influence scapular development and the anatomical locations most strongly affected.…”
Section: Discussionmentioning
confidence: 99%